The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2217/fmb.13.147
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Phenolic Compounds Identified in Flowers from North Eastern Portugal Against Candida Species

Abstract: Aim: To evaluate the antifungal effect of gallic acid, catechin, luteolin and quercetin, phenolic compounds identified from flowers of North Eastern Portugal, against Candida planktonic and biofilm cells. Materials & methods: The MICs were determined in Candida planktonic cells and the effect of phenolic compounds on Candida biofilms was assessed through quantification of colony-forming units. Results: MIC values demonstrated that gallic acid presented the highest effect against all Candida species. Catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 41 publications
(32 reference statements)
6
43
1
3
Order By: Relevance
“…NA: Not available. been proposed that it may act by a disruption of fungi membrane preventing the development of cells [40]. The antifungal effect of gallic acid on Candida albicans and non-albicans was found in previous studies [40][41][42].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…NA: Not available. been proposed that it may act by a disruption of fungi membrane preventing the development of cells [40]. The antifungal effect of gallic acid on Candida albicans and non-albicans was found in previous studies [40][41][42].…”
Section: Discussionmentioning
confidence: 91%
“…Gallic acid is considered a promising antifungal agent in the literature [40]. Its mechanism of action is not fully understood, but it has The concentration required to inhibit the growth in the 50 and 90% of samples (MIC 50 and MIC 90 , respectively) was showed only for clinical species presenting more than ten samples accordingly to Schwarz et al [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…matrine [39], oxymatrine [40], gallic acid [41]), but usually owned nice in vivo antifungal functions (e.g. sodium houttuyfonate [42], baicalein [43]).…”
Section: Discussionmentioning
confidence: 99%
“…Other phenolics present-even in lower doses-in our extract could contribute to the observed fungicidal and microbial effects such as gallic acid which had been proven to possess bactericidal and antifungal activity against F. solani (Nguyen et al, 2015) and Candida species (Alves et al, 2014). Therefore, syringic acidknown to have antimicrobial activity and fungitoxicityas proven against Gano derma boninense by Chong et al (2012) could result in observed antimicrobial effects.…”
Section: Azedarach Extract Had Shown Important Antibacterial Activmentioning
confidence: 92%